Synthesis of Peony-Like Cu(II) Complexes of Schiff Base Derived from 3,4-Dimethoxybenzaldehyde and p-Aminobenzoic Acid - Xu, Qiang; Cai, Yan-Hua; Wang, Feng (Asian Journal of Chemistry, 2013)
Peony-like Cu(II) complexes of Schiff base was synthesized by copper acetate. Schiff base ligand was synthesized by 3,4-dimethoxybenzaldehyde with p-aminobenzoic acid using supersonic speed gas impacting. The synthesized peony-like Cu(II) complexes of Schiff base were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy and thermo-gravimetric analysis. SEM exhibited that the Cu(II) complexes of Schiff base was uniform and the diameter of the peony-like Cu(II) complexes of Schiff base was ca. 10 μm, analysis results reveal that surfactants CTAB plays an interacting important role in the formation of peony-like Cu(II) complexes of Schiff base. TGA indicated that Cu(II) complexes of Schiff base was divided into two steps and the decomposition temperature increased with the increasing of heating rate. The optimized reaction condition was stirring speed 20 rpm, molar ratio of Schiff base ligand: copper acetate 1:3, reaction time 3 h, reaction temperature 70 ºC, the yield was 90.7 %.